Composite material of PDMS with interchangeable transmittance: study of optical, mechanical properties and wettability - Sales, Flaminio Cesar Pereira (2021)
Polydimethylsiloxane (PDMS) is a polymer that has attracted the attention of researchers due to its unique properties such as transparency, biocompatibility, high flexibility, and physical and chemical stability. In addition, PDMS modification and combination with other materials can expand its range of applications. For instance, the ability to perform superhydrophobic coating allows for the manufacture of lenses. However, many of these processes are complex and expensive. One of the most promising modifications, which consists of the development of an interchangeable coating, capable of changing its optical characteristics according to some stimuli, has been underexplored. Thus, we report an experimental study of the mechanical and optical properties and wettability of pure PDMS and of two PDMS composites with the addition of 1% paraffin or beeswax using a gravity casting process. The composites’ tensile strength and hardness were lower when compared with pure PDMS. However, the contact angle was increased, reaching the highest values when using the paraffin additive. Additionally, these composites have shown interesting results for the spectrophotometry tests, i.e., the material changed its optical characteristics when heated, going from opaque at room temperature to transparent, with transmittance around 75%, at 70 °C. As a result, these materials have great potential for use in smart devices, such as sensors, due to its ability to change its transparency at high temperatures.